THE CHARTER OF FUNDAMENTAL RIGHTS OF THE EUROPEAN UNION AS AN INSTRUMENT OF PROTECTION OF HUMAN RIGHTS (Law and world, 2019)
The article is dedicated to the ﬁrst catalogue of human rights at the level of the European Union. Especially it focuses on the issues of judicial protection of the rights declared in the Charter of Fundamental Rights, including the future prospects of the control mechanism of this instrument of human rights protection. The Charter, adopted on 7 December 2000, reﬂects the EU’s aspiration to increase the level and scope of legal protection of fundamental rights and freedoms within the Union. It is distinguished by the simplicity of formulations and unique classiﬁcation of fundamental rights, based not on the subject of the fundamental rights, but on the values, which they protect.